2013
DOI: 10.1124/dmd.112.049676
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Cirrhosis Alters Nuclear Receptor and Drug Transporter Expression in Human Liver

Abstract: Unsafe use of alcohol results in approximately 2.5 million deaths worldwide, with cirrhosis contributing to 16.6% of reported deaths. Serum insulin levels are often elevated in alcoholism and may result in diabetes, which is why alcoholic liver disease and diabetes often are present together. Because there is a sizable population with these diseases alone or in combination, the purpose of this study was to determine whether transporter expression in human liver is affected by alcoholic cirrhosis, diabetes, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 42 publications
(52 reference statements)
4
28
2
1
Order By: Relevance
“…The expression of other transporters was not affected by cirrhosis. These results differ from previous studies in which the mRNA and protein expression of some of these transporters was determined (Ogasawara et al, 2010;More et al, 2013). Ogasawara et al reported that the mRNA expression of BCRP, MATE1, MRP2, MRP3, OATP1B1, 1B3, 2B1, and OCT1 was significantly reduced in hepatitis C cirrhosis livers versus control livers.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The expression of other transporters was not affected by cirrhosis. These results differ from previous studies in which the mRNA and protein expression of some of these transporters was determined (Ogasawara et al, 2010;More et al, 2013). Ogasawara et al reported that the mRNA expression of BCRP, MATE1, MRP2, MRP3, OATP1B1, 1B3, 2B1, and OCT1 was significantly reduced in hepatitis C cirrhosis livers versus control livers.…”
Section: Discussioncontrasting
confidence: 99%
“…Ogasawara et al reported that the mRNA expression of BCRP, MATE1, MRP2, MRP3, OATP1B1, 1B3, 2B1, and OCT1 was significantly reduced in hepatitis C cirrhosis livers versus control livers. Another study, in a limited number of alcoholic cirrhosis livers (n = 10), found that BCRP, MRP1, and MRP3-5 protein expression (but not that of MRP2 or MRP6) was elevated (More et al, 2013). The reasons for the discrepancies between these data and our data are not known but could be differences in ethnicity (Japanese versus Caucasian liver tissues), endpoints (mRNA versus protein expression), and severity of the disease or sample size.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Combined with the results from our study, it is likely that the observed down-regulation of the Nrf2-mediated response in the early study was due to the upregulation of Hrd1 by tunicamycin. Inconsistent with our data, a recent study comparing gene expression profiles from human liver tissues from normal, steatosis, alcohol cirrhosis, and diabetic cirrhosis showed increased Nrf2 levels and increased downstream genes in alcoholic and diabetic cirrhotic livers compared with normal nonsteatotic livers (More et al 2013). The alcoholic cirrhotic liver tissues used in this study are from the same repository as ours.…”
Section: Discussionsupporting
confidence: 85%
“…Up-regulation of P-gp efflux transporters as an adaptive mechanism to limit the accumulation of toxic biliary constituents has been observed in liver samples from patients with advanced primary biliary cirrhosis [13]. Higher BCRP mRNA and protein expression has also been observed in liver tissue from subjects with alcoholic or diabetic cirrhosis [14]. The up-regulation of these efflux transporters could explain the decrease in ombitasvir exposures in subjects with hepatic impairment in this study.…”
Section: Discussionsupporting
confidence: 56%